Income of Bubu Fishermen in Rajuni Village, Selayar Regency - H., Firga; Tahang, Hamzah (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2025)
This study aims to analyze the income of bubu fishermen on Rajuni Island, Taka Bonerate District, Selayar Islands Regency. This study was conducted from October to December 2024 on Rajuni Island, Taka Bonerate District, Selayar Islands Regency, South Sulawesi Province. This study used a qualitative and quantitative (mixed methods) approach. The qualitative approach was used to obtain descriptive data through in-depth interviews and observations. The sampling method used in this study was purposive sampling, where the samples were selected according to the researcher's preferences from among the population so that the samples taken could match the desired population characteristics. The total number of samples taken was 12 fishing operations using bubu. Data collection was carried out through interviews, literature studies, and documentation. Data analysis was performed using quantitative descriptive analysis. The results of the study show that the fishermen's income level is The average total cost of bubu fishing is IDR 6,573,051 per month, with monthly income varying according to season: IDR 8,266,949 during the peak season, IDR 5,051,949 during the transition season, and IDR 2,701,949 during the lean season.